The Influence of the Debate Method in Learning Pancasila Education on the Emotional Management of Class XI Students - Hasan, Alfiana; Rismawati, Rismawati; Azis, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to examine the effect of the debate method on improving critical thinking skills and emotional regulation of 11th-grade students at UPT SMAN 9 Jeneponto. Using a quantitative approach with a quasi-experimental design, the research involved two classes of 32 students each. The results showed a significant improvement in the experimental class; students with high scores increased from 8 (25%) to 24 (75%), while the control class only increased from 7 (21.88%) to 9 (28.13%). In terms of emotional regulation, 26 students in the experimental class were categorized as good to very good, while the majority in the control class were in the poor category. The debate method proved effective in enhancing critical thinking and emotional regulation skills..